Rehabilitation of Drug Abuse Victims from a Humanist Perspective - Laksana, Andri Winjaya; Argo Victoria, Ong (Law Development Journal, 2025)
Drug abuse is one of the crucial problems faced by the Indonesian nation, not only as a legal issue, but also as a health and human rights issue. In Law Number 35 of 2009 concerning Narcotics, rehabilitation is regulated as a form of treatment for addicts. However, there is still ambiguity regarding the status of rehabilitation: whether it is a right that must be guaranteed by the state, or an obligation that must be carried out by addicts. This article aims to analyze the position of rehabilitation in the perspective of Indonesian positive law and examine the concept within the framework of human rights. The method used is normative juridical with a legislative and conceptual approach. The results of the study indicate that rehabilitation should be positioned as a fundamental right guaranteed by the state in order to fulfill the right to health, as well as being a more humane alternative to criminal punishment. The results of this study indicate that interpersonal communication built between counselors and drug addict patients uses a humanistic approach, including (1) Approaching Drug Addict Patients to Foster an Open Attitude, which is very influential in fostering effective interpersonal communication between counselors and addicts. (2) Cultivating an Attitude of Empathy, Counselors towards patients or vice versa, as a willingness to understand others completely both what is visible and what is contained, both in the aspects of feelings, thoughts and desires, when empathy grows in the interpersonal communication process, then the atmosphere of the communication relationship will be able to develop and grow an attitude of mutual understanding and acceptance, (3) Cultivating Positive Feelings in patients/clients, the success of interpersonal communication depends a lot on the quality of one's views and feelings; positive or negative. Positive views and feelings about oneself, towards counselors to addicts or vice versa will give rise to positive interpersonal communication behavior patterns as well. (4) Providing Encouragement and Support, providing encouragement or kindling of enthusiasm from counselors to addicts, so that with support in this situation, interpersonal communication will last a long time because a supportive atmosphere is created.